Feedback : Exergy exergesis. (2nd March 2016) - Fisk, David; Smith, Ray
Abstract: In reply to the news article "Exergy: less heat, more light" (December 2015 pp10–11) about the efforts of a group of scientists within Science Europe (an umbrella organization for European research agencies) to redefine efficiency in terms of exergy, which the article described as "energy that can be used to do work, or…useful energy".